Brazil–colombia: security and trade strengthen their far vicinity (2006)
Colombia shares with Brazil the one that constitutes its second frontier in extension, but, contrary to the most extensive that separates it and it communicates with Venezuela, to that boundary he/she has not been granted in the country the relevance that deserves, in spite of being located in such a strategic region as the Amazonia, nevertheless its neighbor’s enormous geopolitical and economic weight and although some areas of that frontier have been and they continue being articulate, in an or another way, to international and global flows. Yesterday histories and of today they have impacted so that the two political centers, Brasilia and Bogotá, behave as distant, unknown and fearful neighbors, and that only in the last years they come closer mutually, urged by the safe-deposit problems and motivated by the global commercial or geopolitical interest.